A Ming Chinese and Spanish Imperial Collaboration in Southeast Asia: The Boxer Codex. Issue 4 (24th November 2022) - Nelson, Jennifer
Abstract: The Boxer Codex is a ca. 1591 compilation of accounts, written in or translated into Spanish, of the peoples of Southeast Asia alongside illustrations made by a Christian Sangley (Manila Chinese) artist. Scholars should understand this work not as hybrid but as a collaboration between imperial cultures. Evidence of the self-portrait of the artist as a Christianized Sangley and the earliest-known image of a bayoguin, a Tagalog man operating as a female spiritual, medical, and community leader, suggests the rewards of attending to the visual rhetorics of colonization alongside current scholarly emphases on materiality and trade.